Accesibilidad universal en entornos peatonales. Plataforma 1 PIT 01 de la ciudad de Ambato. - García Vaicilla, Anderson Gualberto (2024)
Urban pedestrian environments are essential for the development of life in cities. These public spaces, par excellence, must be conceived as accessible to everyone. As cities grow, it is essential to address the problems and deficiencies that limit the full participation of all citizens, especially those people who have some type of disability. In this context, the present study, focused on Platform 1 PIT 01 of the city of Ambato, aims to establish accessible design criteria for the spaces that are included in accessibility chain 1, corresponding to the pedestrian area limited to the entrance of the buildings. The methodology adopted includes the collection of information through the perception of space by people with disabilities, the consultation of professional experts and workers enrolled in projects that involve accessible design, and the diagnosis of the existing infrastructure within the delimited area. , which is supported by a quantitative evaluation. As a result, a universal accessibility guide is developed, which incorporates important theoretical information about accessibility and the subtopics that are intertwined with it, a description of the methodology used and the implementation of accessible design criteria based on the standards established by the regulations. national and international, which later allow the development of a case study, in which these criteria are incorporated to improve the percentage of accessibility on a street within the established urban area